Vitamin D levels during and after resolution of ketoacidosis in children with new onset Type 1 diabetes. Issue 7 (21st May 2013) - Devidayal,; Singh, M. K.; Sachdeva, N.; Singhi, S.; Attri, S. V.; Jayashree, M.; Bhalla, A. K.
Abstract Aim To study the effect of ketoacidosis on measured 25‐hydroxyvitamin D3 in children with new onset Type 1 diabetes. Methods Measurement of pH and bicarbonate levels was carried out in children with newly diagnosed Type 1 diabetes at presentation with ketoacidosis. 25‐hydroxyvitamin D3 estimation was carried out at presentation (timepoint 1) and 1 month later (timepoint 2). There was no significant difference in the mean (±sd) 25‐hydroxyvitamin D3 levels [35.39 (±25.79) vs 39.63 (±48.03) nmol/L; P = 0.661) at the two timepoints in the study. Results Correlation analysis revealed a positive correlation between bicarbonate levels and timepoint 1, i.e. the lower the bicarbonate levels, the lower were the timepoint 1 levels and vice versa (correlation coefficient 0.538, P = 0.001). Timepoint 2 levels also showed a positive correlation with serum bicarbonate levels with a correlation coefficient of 0.379 (P = 0.032). None of the variables other than bicarbonate, .(age, gender, BMI, pH or time), was found to have the predictive ability for timepoint1 levels. Similarly for predicting timepoint 2 levels, BMI was found to have independent predictive ability in addition to bicarbonate. Conclusions Severe ketoacidosis, as judged by bicarbonate but not pH, may transiently lower 25‐hydroxyvitamin D3 levels in children with new onset Type 1 diabetes. Persistence of low 25‐hydroxyvitamin D3 levels after resolution of ketoacidosis suggests a state of permanent vitamin D deficiency in our patient population.